Ice Complex formation on Bol'shoy Lyakhovsky Island (New Siberian Archipelago, East Siberian Arctic) since about 200 ka. Issue 2 (September 2019) - Wetterich, Sebastian; Rudaya, Natalia; Kuznetsov, Vladislav; Maksimov, Fedor; Opel, Thomas; Meyer, Hanno; Günther, Frank; Bobrov, Anatoly; Raschke, Elena; Zimmermann, Heike H.; Strauss, Jens; Starikova, Anna; et al.
Abstract: Late Quaternary landscapes of unglaciated Beringia were largely shaped by ice-wedge polygon tundra. Ice Complex (IC) strata preserve such ancient polygon formations. Here we report on the Yukagir IC from Bol'shoy Lyakhovsky Island in northeastern Siberia and suggest that new radioisotope disequilibria ( 230 Th/U) dates of the Yukagir IC peat confirm its formation during the Marine Oxygen Isotope Stage (MIS) 7a–c interglacial period. The preservation of the ice-rich Yukagir IC proves its resilience to last interglacial and late glacial–Holocene warming. This study compares the Yukagir IC to IC strata of MIS 5, MIS 3, and MIS 2 ages exposed on Bol'shoy Lyakhovsky Island. Besides high intrasedimental ice content and syngenetic ice wedges intersecting silts, sandy silts, the Yukagir IC is characterized by high organic matter (OM) accumulation and low OM decomposition of a distinctive Drepanocladus moss-peat. The Yukagir IC pollen data reveal grass-shrub-moss tundra indicating rather wet summer conditions similar to modern ones. The stable isotope composition of Yukagir IC wedge ice is similar to those of the MIS 5 and MIS 3 ICs pointing to similar atmospheric moisture generation and transport patterns in winter. IC data from glacial and interglacial periods provide insights into permafrost and climate dynamics since about 200 ka.